Dibenzo[a,c]cyclooctadiene lignans of the genus Schisandra: importance, isolation and determination - Opletal, Lubomír; Sovová, Helena; Bártlová, Milena (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2004)
The drug Wuweizi (dried fruits of Schisandra chinensis or S. sphenantherd) is one of important medicinal means used in the Oriental medicine. The lignans of dibenzo[a,c]cyklooctadiene type are major constituents, a volatile oil with mono- and ses-quiterpens, an oil, organic acids and small amounts of additional compounds are also present. The content of major lignans (schizandrin, deoxyschizandrin, gomisin A, gomisin N, gamma-schizandrin, wuweizisu C) in commercially available drugs ranges usually between 3 and 5%. The present paper biefly comments the isolation and biological activity of the lignans and is especially concerned with analytical methods (TLC and HPLC) for the determination of the drug fingerprint and methods for the determination of constituents in drugs, mixtures and biological materials. HPLC methods using RP-silica bonded phases and diluted methanol, acetonitrile (or a mixture of both), are most important for these purposes. Electromigration methods are less suitable and the importance of hyphenation procedures is practically negligible.
Keywords: chromatografie na tenké vrstvě; Chromatography, High Pressure Liquid; cyklooktany; Chromatography, Thin Layer; lignany; Cyclooctanes; Schisandra; Lignans; vysokoúčinná kapalinová chromatografie